Development of propulsion control system for surface vehicle - Tripathi, Avi (Nanyang Technological University, 2022)
This paper, titled “Development of Propulsion Control System for Surface Vehicle”, is based on the Maritime RobotX Challenge 2022. The RobotX challenge is a biennial competition, that invites students from universities to build an Unmanned Surface Vehicle on the Wave-Adaptive Modular Vessel platform. NTU participated in this competition in the year 2014. However, for the 2022 entry, an improved variant of the propulsion system and control system is necessary to increase the chances of success in the competition. This report analyses the propulsion system used by NTU in the past, and surveys the solutions deployed by other teams, to understand what NTU’s solution lacked. The identified issue is to do with the control strategy used by the NTU team in the past. To resolve this, a new set of potential solutions are considered. These include common commercial solutions and a custom solution using the waterjet propulsion technology. The solutions are then pitted against each other using an evaluation table to identify the most appropriate solution for NTU. A recommended solution is proposed, for both hardware and control. The necessary hardware components are highlighted and a control system, with an inner control loop for the propulsion motors, is outlined. Eventually, a scaled-down version of the system is tested to determine potential barriers and understand the viability of the proposed solution. The report ends by suggesting further work that could complete the entire propulsion setup.